The Evolution of Minimum Revenue Guarantees (MRGs) in PPP Infrastructure Investment - Ali Sunandar; Fitri Andriyanti; Saipol Bari Abd Karim; Umi Kalsum Zolkafli Zulkifly (Journal of Civil Engineering, 2026)
This study investigates the evolution of minimum revenue guarantees (MRGs) in public-private partnership (PPP) infrastructure investment, tracing their development from basic risk mitigation instruments to dynamic, strategically optimized, and sustainability oriented financial mechanisms. A qualitative research design was employed using systematic thematic synthesis of peer reviewed literature indexed in Scopus and Web of Science (WoS) up to February 2026. The review screened 415 records and identified 44 eligible articles for analysis, comprising 5 studies published up to 2010, 8 during 2011 to 2015, 16 during 2016 to 2020, and 15 during 2021 to 2026. The findings reveal four evolutionary phases characterized by advances in real options valuation, risk sharing optimization, game theoretic contract design, adaptive profit distribution, and sustainability focused applications. The study proposes a unified conceptual framework consisting of three interrelated dimensions: strategic and game theoretic contract optimization, adaptive and performance linked guarantee mechanisms, and sustainability-oriented sector specific financial structuring. The framework contributes to theory by integrating historical and contemporary developments into a comprehensive roadmap for MRG design. Practically, it provides guidance for policymakers and practitioners seeking to balance fiscal sustainability, investor incentives, and long-term infrastructure resilience. The study is limited by its reliance on qualitative literature synthesis and highlights opportunities for future empirical, quantitative, and digital finance research to further refine adaptive MRG frameworks.